Identification Fungi from Soil of different places in Baghdad (Journal of the College of Basic Education, 2022)
The present study deals with isolation and characterization of fungi from different soil samples including: agricultural, fields, gardens, petroleum and cattle soil ) from Baghdad . The fungi have been isolated and identified by using two methods: direct isolation (soil plate method) and soil dilution method, using sabouraud’s dextrose agar (SDA). also the fungi have been examined microscopically with Lacto phenol cotton blue dye ,to determine the genus of the fungi isolates. The results were: 89 fungal isolates have been identified, and the results have shown that the highest percentage of fungi isolates was penicilium with 38.2%, followed by Mucur with 23.59%. The third one in the isolation percentage was alternaria with 14.6%, while yeast, Rhizopus, Fusarium and Aspergillus had the isolation percentages: 8.98% , 3.37% , 6.74% and 4.49% respectively.